Regulation of biological processes by ubiquitin ligases: a focus on the Pagano Lab’s contribution - Kaldis, Philipp; Porter, Lisa A. (Frontiers in Cell and Developmental Biology, 2024)
Protein homeostasis depends on many fundamental processes including mRNA synthesis, translation, post-translational modifications, and proteolysis. In the late 70s and early 80s the discovery that the small 76 amino acid protein ubiquitin could be attached to target proteins via a multi-stage process involving ubiquitin-activating enzymes, ubiquitin conjugating enzymes, and ubiquitin ligases, revealed an exciting new post-translational mechanism to regulate protein degradation. This cellular system was uncovered using biochemical methods by Avram Hershko, who would later won the Nobel prize for this discovery; however, the biological functions of ubiquitin ligases remained unknown for many years. It was initially described that ubiquitin modifies proteins at one or more lysine residues and once a long ubiquitin chain was assembled, proteins were degraded by the proteasome. Now we know that proteins can be mono-, multimono-, homotypic poly-, or heterotypic poly-ubiquitylated, each of which confers a specific signal that goes beyond protein degradation regulating additional key cellular functions such as signal transduction, protein localization, recognition of damaged proteins, etc.